Influência do tamanho da muda de abacaxizeiro, Ananas cosomus (L.) Merr, sobre o número e sobre o peso médio dos frutos - Fortes, José Maurício; Andersen, Otto; Maffia de Oliveira, Laede; V R Pinheiro, Rubens (Revista Ceres, 2025)
The objective of this study was to observe the effect of the size of planting material (slips) upon the number and mean weight of the fruit produced.